PENGARUH POPULARITAS MEREK DAN CONTENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK UMKM LOTION RACCA BEAUTY MELALUI MEDIA SOSIAL DI KOTA BANJARMASIN - Hairudinor; Fitriyadi; Humaidi; Siti Aulia Rahmawati (Smart Business Journal (SBJ), 2024)
The purpose of this study is to ascertain and evaluate the impact of content marketing and brand popularity on decisions made by consumers to buy MSME Lotion Racca Beauty items on social media in the city of Banjarmasin. This study employs a quantitative methodology, and up to 100 respondents who have purchased Racca Beauty Lotion items in Banjarmasin between the ages of 17 and older make up the sample. This technique is known as accidental sampling. A questionnaire is used for data collecting, and IBM SPSS Statistics version 25 is used for data analysis through multiple linear regression for hypothesis testing. The study's findings indicate that: (1) The decision to purchase Racca Beauty Lotion in the city of Banjarmasin is positively and significantly influenced by brand popularity; (2) The decision to purchase Racca Beauty Lotion in the city of Banjarmasin is positively and significantly influenced by content marketing; and (3) Product quality and content marketing have a simultaneous influence on decisions to purchase Racca Beauty Lotion in the city of Banjarmasin.